Prevalence of antibiotic prescription in southern Italian outpatients: real-world data analysis of socioeconomic and sociodemographic variables at a municipality level - Russo V; Monetti VM; Guerriero F; Trama U; Guida A; Menditto E; Orlando V (Dove Medical Press, 2018)
Veronica Russo,1,* Valeria Marina Monetti,1,* Francesca Guerriero,1 Ugo Trama,2 Antonella Guida,3 Enrica Menditto,1 Valentina Orlando1 1CIRFF, Center of Pharmacoeconomics, University of Naples Federico II, 2Regional Pharmaceutical Unit, 3Directorate-General for Protection of Health, Campania Region, Naples, Italy *These authors contributed equally to this work Purpose: The aim of this study was to analyze the geographic variation in systemic antibiotic prescription at a regional level and to explore the influence of socioeconomic and sociodemographic variables.Methods: This study was a retrospective analysis of reimbursement pharmacy records in the outpatient settings of Italy’s Campania Region in 2016. Standardized antibiotic prescription rates were calculated at municipality and Local Health Unit (LHU) level. Antibiotic consumption was analyzed as defined daily doses (DDD)/1000 inhabitants per day (DID). Logistic regression was performed to evaluate the association between antibiotic prescription and sociodemographic and socioeconomic determinants at a municipality level.Results: The average antibiotic prevalence rate was 46.8%. At LHU level, the age-adjusted prevalence rates ranged from 41.1% in Benevento to 51.0% in Naples2. Significant differences were found among municipalities, from 15.2% in Omignano (Salerno LHU [Sa-LHU]) to 61.9% in Moschiano (Avellino [Av-LHU]). The geographic distribution also showed significant differences in terms of antibiotic consumption, from 6.7 DID in Omignano to 41.6 in San Marcelino (Caserta [Ce-LHU]). Logistic regression showed that both municipality type and average annual income level were the main determinants of antibiotic prescription. Urban municipalities were more than eight times as likely to have antibiotic high prevalence rates compared to rural municipalities (adjusted odds ratio [OR]: 8.62; 95% confidence interval [CI]: 4.06–18.30, P<0.001). Low average annual income level municipalities were more than eight times as likely to have antibiotic high prevalence rates compared to high average annual income level municipalities (adjusted OR: 8.48; 95% CI: 3.45–20.81, P<0.001).Conclusion: We provide a snapshot of Campania’s antibiotic consumption, evidencing the impact of both socioeconomic and sociodemographic factors on the prevalence of antibiotic prescription. The observed intraregional variability underlines the lack of shared therapeutic protocols and the need for careful monitoring. Our results can be useful for decision makers to plan educational interventions, thus optimizing health resources and improving rational drug use. Keywords: retrospective databases, drug utilization, appropriateness